Sex specific gut bacterial community structure: implications for frailty risk in people with HIV - Aline Zaparte; John W. Lammons; Christopher M. Taylor; Meng Luo; Hui-Yi Lin; Robert W. Siggins; Patricia E. Molina; David A. Welsh (GeroScience, 2025)

Microbial ecology in hypersaline coastal lagoons: A model for climate-induced coastal salinisation and eutrophication - Christopher Keneally; Virginie Gaget; Daniel Chilton; Stephen P. Kidd; Luke Mosley; David T. Welsh; Yongqiang Zhou; Lei Zhou; Justin Brookes (Earth-Science Reviews, 2025)

Understanding sediment nutrient cycling in a hypersaline coastal lagoon using hydrogel-based passive sampling techniques - Jianyin Huang; Orlando Lam-Gordillo; Luke M. Mosley; Christopher Keneally; Justin Brookes; David T. Welsh (Marine Pollution Bulletin, 2025)

Analysis of nonsynonymous SNPs in candidate genes that influence bovine temperament and evaluation of their effect in Brahman cattle - Gilberto Ruiz-De-La-Cruz; Ana María Sifuentes-Rincón; Francisco Alejandro Paredes-Sánchez; Gaspar Manuel Parra-Bracamonte; Eduardo Casas; David G. Riley; George A. Perry; Thomas H. Welsh; Ronald D. Randel (Molecular Biology Reports, 2024)
Background Temperament is an important production trait in cattle and multiple strategies had been developed to generate molecular markers to assist animal selection. As nonsynonymous single nucleotide polymorphisms are markers with the potential to affect gene functions, they could be useful to predict phenotypic effects. Genetic selection of less stress-responsive, temperamental animals is desirable from an economic and welfare point of view. Methods and results Two nonsynonymous single nucleotide polymorphisms identified in HTR1B and SLC18A2 candidate genes for temperament were analyzed in silico to determine their effects on protein structure. Those nsSNPs allowing changes in proteins were selected for a temperament association analysis in a Brahman population. Transversion effects on protein structure were evaluated in silico for each amino acid change model, revealing structural changes in the proteins of the HTR1B and SLC18A2 genes. The selected nsSNPs were genotyped in a Brahman population ( n = 138), and their genotypic effects on three temperament traits were analyzed: exit velocity, pen score, and temperament score. Only the SNP rs209984404-HTR1B (C/A) showed a significant association ( P = 0.0144) with pen score. The heterozygous genotype showed a pen score value 1.17 points lower than that of the homozygous CC genotype. Conclusion The results showed that in silico analysis could direct the selection of nsSNPs with the potential to change the protein. Non-synonymous single nucleotide polymorphisms causing structural changes and reduced protein stability were identified. Only rs209984404-HTR1B shows that the allele affecting protein stability was associated with the genotype linked to docility in cattle.

Trace metal distribution in seagrass-vegetated sediments of an urbanized estuary in Queensland, Australia - Heera Lee; Clare Morrison; Nicholas J.C. Doriean; David T. Welsh; William W. Bennett (Marine Pollution Bulletin, 2024)

Organic matter accumulation drives methylotrophic methanogenesis and microbial ecology in a hypersaline coastal lagoon - Christopher Keneally; Matilda Southgate; Daniel Chilton; Virginie Gaget; David T. Welsh; Luke Mosley; Dirk V. Erler; Stephen P. Kidd; Justin Brookes (Limnology and Oceanography, 2024)
Hypersalinity is common in coastal wetlands throughout warm, tropical, and arid regions. Climate‐induced changes in rainfall, sea level, and anthropogenic modification to basins and coastlines are likely to further increase salinization in these ecosystems. Yet, carbon cycling in hypersaline coastal wetlands is not well understood, and poorly constrained in climate models. In the Coorong, a eutrophic, hypersaline coastal lagoon, recognized as internationally important under the Ramsar convention, organic matter rapidly accumulates in deeper areas of the lagoon, through the settling of fine detrital particles, phytoplankton and suspended sediments. During initial surveys, elevated surface water methane (CH 4 ) concentrations were observed above these fine depositional sediments. To identify the drivers of CH 4 production, organic matter and sediment characteristics were assessed in surface sediments. Genetic markers (i.e., 16rDNA and the mcrA functional gene) were used to characterize microbial communities. With multiple lines of evidence, this study identifies organic matter, methanogen abundance, and salinity as important drivers of CH 4 production, which is concentrated in depositional zones. Archaea were also more abundant in depositional zones, including methylotrophic methanogens: Methanofastidiosales, Methanomasiliicoccales, Methermicoccaceae , and Methanococcoides . These methanogens were highly correlated to CH 4 in porewater, suggesting an influence of methylotrophic methanogenesis. To investigate further, metabolic genes were predicted from 16S rRNA with PICRUSt2. This represents the first effort to analyze CH 4 dynamics in the Coorong, underscoring the need to integrate these unique ecosystems into global climate models to enhance our understanding of greenhouse gas dynamics and emissions in a changing climate.

Reductive sorption of vanadium by iron monosulfide in seawater - Felicia J. Haase; Colton J. Vessey; Ryo Sekine; Nicholas J.C. Doriean; David T. Welsh; Joseph A. Otte; Jessica Hamilton; Donald E. Canfield; Yun Wang; Enzo Lombi; William W. Bennett (Chemical Geology, 2024)

Non-linear effects of non-host diversity on the removal of free-living infective stages of parasites - Jennifer E. Welsh; Mirjana Markovic; Jaap van der Meer; David W. Thieltges (Oecologia, 2024)
Among the ecological functions and services of biodiversity is the potential buffering of diseases through dilution effects where increased biodiversity results in a reduction in disease risk for humans and wildlife hosts. Whether such effects are a universal phenomenon is still under intense debate and diversity effects are little studied in cases when non-host organisms remove free-living parasite stages during their transmission from one host to the next by consumption or physical obstruction. Here, we investigated non-host diversity effects on the removal of cercarial stages of trematodes, ubiquitous parasites in aquatic ecosystems. In laboratory experiments using response surface designs, varying both diversity and density at same time, we compared three combinations of two non-hosts at four density levels: predatory crabs that actively remove cercariae from the water column via their mouth parts and gills, filter feeding oysters that passively filter cercariae from the water column while not becoming infected themselves, and seaweed which physically obstructs cercariae. The addition of a second non-host did not generally result in increased parasite removal but neutralised, amplified or reduced the parasite removal exerted by the first non-host, depending on the density and non-host combination. These non-linear non-host diversity effects were probably driven by intra- and interspecific interactions and suggest the need to integrate non-host diversity effects in understanding the links between community diversity and infection risk.

Reductive sorption of vanadium by green rust in seawater - Felicia J. Haase; Colton J. Vessey; Ryo Sekine; David Welsh; Jessica Hamilton; Yun Wang; Jessica White; Donald E. Canfield; Enzo Lombi; William W. Bennett (Geochimica et Cosmochimica Acta, 2023)

Monitoring population-level foraging distribution of a marine migratory species from land: strengths and weaknesses of the isotopic approach on the Northwest Atlantic loggerhead turtle aggregation - Simona A. Ceriani; Susan Murasko; David S. Addison; David Anderson; Greg Curry; Nicole A. Desjardin; Scott F. Eastman; Daniel R. Evans; Nancy Evou; Mariana M. P. B. Fuentes; Matthew H. Godfrey; Kristen M. Hart; et al. (Frontiers in Marine Science, 2023)
Assessing the linkage between breeding and non-breeding areas has important implications for understanding the fundamental biology of and conserving animal species. This is a challenging task for marine species, and in sea turtles a combination of stable isotope analysis (SIA) and satellite telemetry has been increasingly used. The Northwest Atlantic (NWA) loggerhead ( Caretta caretta ) Regional Management Unit, one of the largest sea turtle populations in the world, provides an excellent opportunity to investigate key biological patterns as well as methodological aspects related to the use of stable isotopes to infer spatial distribution of turtles in foraging areas. We provide the first comprehensive assessment of the annual distribution of NWA adult female loggerheads among foraging areas and investigate the efficacy of various analytical approaches as well as the effect of sample size in these types of studies. A total of 5168 individual females were sampled from seven Management Units (MUs) between 2013-2018. We provide the first estimate of the proportion of females originating from each MU that uses each foraging area and show how this proportion varies over time. We also estimate the relative importance (in terms of number of turtles) of each foraging area to the overall loggerhead breeding aggregation nesting in Florida and in the NWA for each year of the study. The foraging area used by reproductively active females differs considerably across MUs. One of these, the Subtropical NWA, is by far the most important foraging area in terms of both number of individuals and genetic diversity, and therefore this region may be considered as a conservation priority. Through simulations, we show that limited sizes of sample groups (unknowns; training; priors) may result in false geographic differentiation and consequently mislead interpretations. We provide thresholds and methodological recommendations for future studies. This study establishes a fundamental baseline for monitoring the annual contribution of foraging area to a terrestrial-based breeding aggregation of a marine animal in a cost-effective way. This type of monitoring allows for early detection of changes in foraging distributions—a possible effect of climate change on marine ecosystems or of area-specific anthropogenic threats.

Metals in coastal seagrass habitats: A systematic quantitative literature review - Heera Lee; Clare Morrison; Nicholas J. C. Doriean; David T. Welsh; William W. Bennett (Critical Reviews in Environmental Science and Technology, 2023)

The spontaneous mouse mutant low set ears (Lse) is caused by tandem duplication of Fgf3 and Fgf4 - Alana Luzzio; Sarah Edie; Kristina Palmer; L. Brianna Caddle; Rachel Urban; Leslie O. Goodwin; Ian C. Welsh; Laura G. Reinholdt; David E. Bergstrom; Timothy C. Cox; Leah Rae Donahue; Stephen A. Murray (Mammalian Genome, 2023)

Correction: A well-studied parasitoid fly of field crickets uses multiple alternative hosts in its introduced range - E. Dale Broder; James H. Gallagher; Aaron W. Wikle; Gabrielle T. Welsh; David M. Zonana; Thomas J. Firneno; Robin M. Tinghitella (Evolutionary Ecology, 2023)

A well-studied parasitoid fly of field crickets uses multiple alternative hosts in its introduced range - E Dale Broder; James H Gallagher; Aaron W Wikle; Gabrielle T Welsh; David M Zonana; Thomas J Firneno; Robin M Tinghitella (Evolutionary Ecology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Denitrification, anammox, and dissimilatory nitrate reduction to ammonium across a mosaic of estuarine benthic habitats - Jian‐Jhih Chen; Dirk V. Erler; Naomi S. Wells; Jianyin Huang; David T. Welsh; Bradley D. Eyre (Limnology and Oceanography, 2021)
Estuaries play a key role in moderating the flow of nitrogen (N) to marine ecosystems. However, the magnitude of this N removal can vary dramatically both within and between estuaries due to the benthic habitats present. Here, we compare denitrification, coupled nitrification–denitrification, anammox, and dissimilatory nitrate reduction to ammonium (DNRA) across a mosaic of benthic habitats in the subtropical Noosa River Estuary, Australia. Using 15 N tracer techniques and passive pore‐water samplers, we show that coupled nitrification–denitrification was the dominant pathway for N 2 production across all habitats, with higher rates in vegetated habitats (10–70 μ mol N m −2 h −1 ) compared to bare sediments (0.9–2 μ mol N m −2 h −1 ). Unusual pore‐water profiles in the macroalgal sediments suggest the presence of sulfur‐driven anoxic nitrification of NH 4 + to NO 3 − and N 2 . A benthic N budget showed that combined denitrification and coupled nitrification–denitrification accounted approximately 96% of the N 2 production, while DNRA accounted for 9% of total NO 3 − reduction pathways in the Noosa River Estuary. The macroalgae habitat contributed 76% of total N removal via N 2 production and 65% of N retention via DNRA, despite accounting for only 25% of the total surface area. We show a strong relationship between seagrass and macroalgae area and N 2 production ( r 2 = 0.8; p

Effects of the Bioturbating Marine Yabby Trypaea australiensis on Sediment Properties in Sandy Sediments Receiving Mangrove Leaf Litter - Ryan J. K. Dunn; David T. Welsh; Peter R. Teasdale; Franck Gilbert; Jean-Christophe Poggiale; Nathan J. Waltham (Journal of Marine Science and Engineering, 2019)
Laboratory mesocosm incubations were undertaken to investigate the influence of burrowing shrimp Trypaea australiensis (marine yabby) on sediment reworking, physical and chemical sediment characteristics and nutrients in sandy sediments receiving mangrove (Avicennia marina) leaf litter. Mesocosms of sieved, natural T. australiensis inhabited sands, were continually flushed with fresh seawater and pre-incubated for 17 days prior to triplicates being assigned to one of four treatments; sandy sediment (S), sediment + yabbies (S+Y), sediment + leaf litter (organic matter; S+OM) and sediment + yabbies + leaf litter (S+Y+OM) and maintained for 55 days. Mangrove leaf litter was added daily to treatments S+OM and S+Y+OM. Luminophores were added to mesocosms to quantify sediment reworking. Sediment samples were collected after the pre-incubation period from a set of triplicate mesocosms to establish initial conditions prior to the imposition of the treatments and from the treatment mesocosms at the conclusion of the 55-day incubation period. Yabbies demonstrated a clear effect on sediment topography and leaf litter burial through burrow creation and maintenance, creating mounds on the sediment surface ranging in diameter from 3.4 to 12 cm. Within S+Y+OM sediments leaf litter was consistently removed from the surface to sub-surface layers with only 7.5% ± 3.6% of the total mass of leaf detritus added to the mesocosms remaining at the surface at the end of the 55-day incubation period. Yabbies significantly decreased sediment wet-bulk density and increased porosity. Additionally, T. australiensis significantly reduced sediment bio-available ammonium (NH4+bio) concentrations and altered the shape of the concentration depth profile in comparison to the non-bioturbated mesocosms, indicating influences on nutrient cycling and sediment-water fluxes. No significant changes for mean apparent biodiffusion coefficients (Db) and mean biotransport coefficients (r), were found between the bioturbated S+Y and S+Y+OM mesocosms. The findings of this study provide further evidence that T. australiensis is a key-species in shallow intertidal systems playing an important role as an ‘ecosystem engineer’ in soft-bottom habitats by significantly altering physical and chemical structures and biogeochemical function.

Growing Canopy on a College Campus: Understanding Urban Forest Change through Archival Records and Aerial Photography - Lara A. Roman; Jason P. Fristensky; Theodore S. Eisenman; Eric J. Greenfield; Robert E. Lundgren; Chloe E. Cerwinka; David A. Hewitt; Caitlin C. Welsh (Environmental Management, 2017)

Symbiodinium mitigate the combined effects of hypoxia and acidification on a noncalcifying cnidarian - Shannon G. Klein; Kylie A. Pitt; Matthew R. Nitschke; Samantha Goyen; David T. Welsh; David J. Suggett; Anthony R. Carroll (Global Change Biology, 2017)
Anthropogenic nutrient inputs enhance microbial respiration within many coastal ecosystems, driving concurrent hypoxia and acidification. During photosynthesis, Symbiodinium spp., the microalgal endosymbionts of cnidarians and other marine phyla, produce O 2 and assimilate CO 2 and thus potentially mitigate the exposure of the host to these stresses. However, such a role for Symbiodinium remains untested for noncalcifying cnidarians. We therefore contrasted the fitness of symbiotic and aposymbiotic polyps of a model host jellyfish ( Cassiopea sp.) under reduced O 2 (~2.09 mg/L) and pH (~ 7.63) scenarios in a full‐factorial experiment. Host fitness was characterized as asexual reproduction and their ability to regulate internal pH and Symbiodinium performance characterized by maximum photochemical efficiency, chl a content and cell density. Acidification alone resulted in 58% more asexual reproduction of symbiotic polyps than aposymbiotic polyps (and enhanced Symbiodinium cell density) suggesting Cassiopea sp. fitness was enhanced by CO 2 ‐stimulated Symbiodinium photosynthetic activity. Indeed, greater CO 2 drawdown (elevated pH ) was observed within host tissues of symbiotic polyps under acidification regardless of O 2 conditions. Hypoxia alone produced 22% fewer polyps than ambient conditions regardless of acidification and symbiont status, suggesting Symbiodinium photosynthetic activity did not mitigate its effects. Combined hypoxia and acidification, however, produced similar numbers of symbiotic polyps compared with aposymbiotic kept under ambient conditions, demonstrating that the presence of Symbiodinium was key for mitigating the combined effects of hypoxia and acidification on asexual reproduction. We hypothesize that this mitigation occurred because of reduced photorespiration under elevated CO 2 conditions where increased net O 2 production ameliorates oxygen debt. We show that Symbiodinium play an important role in facilitating enhanced fitness of Cassiopea sp. polyps, and perhaps also other noncalcifying cnidarian hosts, to the ubiquitous effects of ocean acidification. Importantly we highlight that symbiotic, noncalcifying cnidarians may be particularly advantaged in productive coastal waters that are subject to simultaneous hypoxia and acidification.

Short-Term Nitrogen and Phosphorus Release during the Disturbance of Surface Sediments: A Case Study in an Urbanised Estuarine System (Gold Coast Broadwater, Australia) - Ryan Dunn; Nathan Waltham; Peter Teasdale; David Robertson; David Welsh (Journal of Marine Science and Engineering, 2017)
Understanding the effects of sediment disturbances on nutrient loadings is important for the management of estuarine settings. This study investigated the initial influence of sediment disturbance on water column nutrient concentrations in a shallow estuarine setting within the Gold Coast Broadwater, using a laboratory-based approach. Undisturbed sediment cores (200 mm Ø × 330 mm length, plexiglass) were incubated before and after being subjected to a disturbance event, to investigate the effect on the immediate and subsequent short-term water column nutrient concentrations. Sediment NH4+bio and PO43−bio concentrations ranged from 150 to 478 and 1.50 to 8.56 nmol g−1 dry wt, respectively. Water column NH4+ concentrations underwent the greatest increase (>1000% or approx. 14 times greater) immediately following disturbance, with mean effluxes increasing by >300%. Thereafter, water column NH4+ concentrations and efflux rates declined to near initial pre-disturbance concentrations. Water column NH4+ concentrations accounted for 0.58%–5.50% of the depth-integrated sediment NH4+bio concentration, indicating mobilization of the sediment bound exchangeable NH4+. The observed changes in PO43− concentrations and fluxes were much lower in comparison to those observed for N-species. Following disturbance, increases in the water column PO43− concentration accounted for 7.16%–8.22% depth-integrated sediment bioavailable PO43− at +1 and +2 hours, and 5.65% at +7 hours, respectively. These results provide important insight into the potential implications of disturbance events, such as vessel activities and dredging operations, within the case study region, providing information for potential management options and relevant water quality concerns.

Home-range allometry in coral reef fishes: comparison to other vertebrates, methodological issues and management implications - Kirsty L. Nash; Justin Q. Welsh; Nicholas A. J. Graham; David R. Bellwood (Oecologia, 2015)

Influence of Potamogeton pectinatus and microphytobenthos on benthic metabolism, nutrient fluxes and denitrification in a freshwater littoral sediment in an agricultural landscape: N assimilation versus N removal - Daniele Nizzoli; David T. Welsh; Daniele Longhi; Pierluigi Viaroli (Hydrobiologia, 2014)

Characterizing microbial communities and processes in a modern stromatolite ( S hark B ay) using lipid biomarkers and two‐dimensional distributions of porewater solutes - Anais Pagès; Kliti Grice; Michael Vacher; David T. Welsh; Peter R. Teasdale; William W. Bennett; Paul Greenwood (Environmental Microbiology, 2014)
Summary Modern microbial mats are highly complex and dynamic ecosystems. Diffusive equilibration in thin films ( DET ) and diffusive gradients in thin films ( DGT ) samplers were deployed in a modern smooth microbial mat from Shark Bay in order to observe, for the first time, two‐dimensional distributions of porewater solutes during day and night time. Two‐dimensional sulfide and alkalinity distributions revealed a strong spatial heterogeneity and a minor contribution of sulfide to alkalinity. Phosphate distributions were also very heterogeneous, while iron( II ) distributions were quite similar during day and night with a few hotspots of mobilization. Lipid biomarkers from the three successive layers of the mat were also analysed in order to characterize the microbial communities regulating analyte distributions. The major hydrocarbon products detected in all layers included n ‐alkanes and isoprenoids, whilst other important biomarkers included hopanoids. Phospholipid fatty acid profiles revealed a decrease in cyanobacterial markers with depth, whereas sulfate‐reducing bacteria markers increased in abundance in accordance with rising sulfide concentrations with depth. Despite the general depth trends in community structure and physiochemical conditions within the mat, two‐dimensional solute distributions showed considerable small‐scale lateral variability, indicating that the distributions and activities of the microbial communities regulating these solute distributions were equally heterogeneous and complex.

Erratum to: Status and access to the Collaborative Cross population - Catherine E. Welsh; Darla R. Miller; Kenneth F. Manly; Jeremy Wang; Leonard McMillan; Grant Morahan; Richard Mott; Fuad A. Iraqi; David W. Threadgill; Fernando Pardo-Manuel de Villena (Mammalian Genome, 2014)

Evaluation of ionic liquids on phototrophic microbes and their use in biofuel extraction and isolation - Katherine S. Lovejoy; Lauren E. Davis; Lisa M. McClellan; Antonietta M. Lillo; John D. Welsh; Emily N. Schmidt; Claire K. Sanders; Alexander J. Lou; David T. Fox; Andrew T. Koppisch; Rico E. Del Sesto (Journal of Applied Phycology, 2013)

A Comparative Evaluation of Short-Term Streamflow Forecasting Using Time Series Analysis and Rainfall-Runoff Models in eWater Source - Dushmanta Dutta; Wendy D. Welsh; Jai Vaze; Shaun S. H. Kim; David Nicholls (Water Resources Management, 2012)

Status and access to the Collaborative Cross population - Catherine E. Welsh; Darla R. Miller; Kenneth F. Manly; Jeremy Wang; Leonard McMillan; Grant Morahan; Richard Mott; Fuad A. Iraqi; David W. Threadgill; Fernando Pardo-Manuel de Villena (Mammalian Genome, 2012)

Interactive influences of the marine yabby (Trypaea australiensis) and mangrove (Avicennia marina) leaf litter on benthic metabolism and nitrogen cycling in sandy estuarine sediment - Ryan J. K. Dunn; David T. Welsh; Mark A. Jordan; James M. Arthur; Charles J. Lemckert; Peter R. Teasdale (Hydrobiologia, 2012)

Telomere maintenance genes SIRT1 and XRCC6 impact age-related decline in telomere length but only SIRT1 is associated with human longevity - Sangkyu Kim; Xiuhua Bi; Malwina Czarny-Ratajczak; Jianliang Dai; David A. Welsh; Leann Myers; Michael A. Welsch; Katie E. Cherry; Jonathan Arnold; Leonard W. Poon; S. Michal Jazwinski (Biogerontology, 2012)

Seasonal analyses of arbuscular mycorrhizae, nitrogen-fixing bacteria and growth performance of the salt marsh grass Spartina patens - Allana K. Welsh; David J. Burke; Erik P. Hamerlynck; Dittmar Hahn (Plant and Soil, 2010)

In vitro culture of precision-cut testicular tissue as a novel tool for the study of responses to LH - Andy Michael Laughlin; Thomas H. Welsh; Charles C. Love; Dickson D. Varner; Alan R. Parrish; David W. Forrest; Nancy H. Ing (In Vitro Cellular & Developmental Biology - Animal, 2010)

Oxygen and nutrient dynamics of the upside down jellyfish (Cassiopea sp.) and its influence on benthic nutrient exchanges and primary production - David T. Welsh; Ryan J. K. Dunn; Tarik Meziane (Hydrobiologia, 2009)

Top‐down and bottom‐up influences of jellyfish on primary productivity and planktonic assemblages - Elizabeth J. West; Kylie A. Pitt; David T. Welsh; Klaus Koop; David Rissik (Limnology and Oceanography, 2009)
A manipulative mesocosm experiment was done in a saline coastal lake in Australia to compare the top‐down and bottom‐up influences of jellyfish on primary production and planktonic assemblages. We hypothesized that non‐zooxanthellate jellyfish ( Catostylus mosaicus ) would exert both ‘top‐down’ (grazing) and ‘bottom‐up’ (nutrient excretion) effects, whereas zooxanthellate jellyfish ( Phyllorhiza punctata ) would only exert top‐down influences, as their dissolved excretory products are internally recycled to their zooxanthellae rather than released into the water column. Experimental treatments consisted of triplicate mesocosms that contained two C. mosaicus, two P. punctata, a combination of C. mosaicus and P. punctata , no jellyfish, and an open‐water control (sampling outside mesocosms). Both species of jellyfish preyed heavily on mesozooplankton, initiating a topdown trophic cascade that resulted in increased production of the heterotrophic dinoflagellate Protoperidinium sp. However, no increase in primary production or phytoplankton biomass was observed in the treatments containing P. punctata , indicating that top‐down processes did not extend to primary producers. Bottom‐up excretion of nutrients, however, caused phytoplankton biomass to more than double in the C. mosaicus treatment compared to all other treatments. Increased primary production was due largely to a 10‐fold increase in the diatom Chaetoceros sp. and was predominantly driven by C. mosaicus excreting phosphate (PO 4 3‐ ), which was the limiting nutrient in the lake. Blooms of both zooxanthellate and non‐zooxanthellate jellyfish will deplete mesozooplankton and alter the composition of microzooplankton assemblages via top‐down processes. Excretion of nutrients by blooms of non‐zooxanthellate jellyfish, however, can also greatly increase phytoplankton production and could favor algal blooms.

Limits of single-cell autonomy in the suprachiasmatic nucleus - David K Welsh (Sleep and Biological Rhythms, 2009)

Application of Screening Methods, Shape Signatures and Engineered Biosensors in Early Drug Discovery Process - Izabela Hartman; Alison R. Gillies; Sonia Arora; Christina Andaya; Nitya Royapet; William J. Welsh; David W. Wood; Randy J. Zauhar (Pharmaceutical Research, 2009)

Influence of natural amphipod (Victoriopisa australiensis) (Chilton, 1923) population densities on benthic metabolism, nutrient fluxes, denitrification and DNRA in sub-tropical estuarine sediment - Ryan J. K. Dunn; David T. Welsh; Mark A. Jordan; Peter R. Teasdale; Charles J. Lemckert (Hydrobiologia, 2009)

Influence of decomposing jellyfish on the sediment oxygen demand and nutrient dynamics - Elizabeth Jane West; David Thomas Welsh; Kylie Anne Pitt (Hydrobiologia, 2009)

Influence of jellyfish blooms on carbon, nitrogen and phosphorus cycling and plankton production - Kylie A. Pitt; David T. Welsh; Robert H. Condon (Hydrobiologia, 2009)

Impacts of mussel (Mytilus galloprovincialis) farming on oxygen consumption and nutrient recycling in a eutrophic coastal lagoon - Daniele Nizzoli; David T. Welsh; Marco Bartoli; Pierluigi Viaroli (Hydrobiologia, 2005)

Benthic Fluxes of Dissolved Inorganic Nitrogen in a Coastal Lagoon of the Northern Adriatic Sea: an Interpretation of Spatial Variability Based on Sediment Features and Infauna Activity - Daniele Nizzoli; Giuseppe Castaldelli; Marco Bartoli; David Thomas Welsh; Patricia Arriaga Gomez; Anna Elisa Fano; Pierluigi Viaroli (Marine Ecology, 2002)
Dark respiration rates, dissolved inorganic nitrogen (DIN) fluxes and nitrification rates were measured at two sites in the microtidal Sacca di Goro lagoon in September 2000. DIN fluxes correlated with the biomass of the dominant macrofauna species (the amphipod Corophium spp. at station Giralda and the polychaete Neanthes spp. at station Faro). Respiration (> 6 mmol O 2 m −2 h −1 ) and ammonium fluxes (> 80μmol N m −2 h −1 ) were higher at station Giralda despite the lower organic matter content (4.5 %) and lower macrofauna biomass (4 g AFDW m −2 ). At both sites ammonium fluxes were significantly correlated with the biomass of the benthic infauna, but Corophium stimulated ammonium NH 4 + fluxes 3‐fold compared to Neanthes. The amphipod also enhanced nitrification rates (> 300 μmol N m −2 h −1 ) due to the high density of its burrows, the higher NH 4 + regeneration rates and the enhanced oxygen supply to the bacteria.

Conservation Value and Rankings of Exotic Species - Erica H. Dunn; David J. T. Hussell; Daniel A. Welsh (Conservation Biology, 2001)

SEM Imaging Predicts Quality of Niosomes from Maltodextrin-Based Proniosomes - Almira I. Blazek–Welsh; David G. Rhodes (Pharmaceutical Research, 2001)

Sulphate reduction and nitrogen fixation rates associated with roots, rhizomes and sediments from Zostera noltii and Spartina maritima meadows - Lise B. Nielsen; Kai Finster; David T. Welsh; Andrew Donelly; Rodney A. Herbert; Rutger De Wit; Bente AA. Lomstein (Environmental Microbiology, 2001)
Sulphate reduction rates (SRR) and nitrogen fixation rates (NFR) associated with isolated roots, rhizomes and sediment from the rhizosphere of the marine macrophytes Zostera noltii and Spartina maritima , and the presence and distribution of Bacteria on the roots and rhizomes, were investigated. Between 1‰ and 3‰ of the surface area of the roots and rhizomes of both macrophytes were colonized by Bacteria. Bacteria on the surfaces of S. maritima roots and rhizomes were evenly distributed, while the distribution of Bacteria on Z. noltii roots and rhizomes was patchy. Root‐ and rhizome‐associated SRR and NFR were always higher than rates in the bulk sediment. In particular, nitrogen fixation associated with the roots and rhizomes was 41–650‐fold higher than in the bulk sediment. Despite the fact that sulphate reduction was elevated on roots and rhizomes compared with bulk sediment, the contribution of plant‐associated sulphate reduction to overall sulphate reduction was small (≤ 11%). In contrast, nitrogen fixation associated with the roots and rhizomes accounted for 31% and 91% of the nitrogen fixed in the rhizosphere of Z. noltii and S. maritima respectively. In addition, plant‐associated nitrogen fixation could supply 37–1613% of the nitrogen needed by the sulphate‐reducing community. Sucrose stimulated nitrogen fixation and sulphate reduction significantly in the root and rhizome compartments of both macrophytes, but not in the bulk sediment.

Short-term influence of recolonisation by the polycheate worm [2pt] Nereis succinea on oxygen and nitrogen fluxes and [2pt] denitrification: a microcosm simulation - Marco Bartoli; Daniele Nizzoli; David T. Welsh; Pierluigi Viaroli (Hydrobiologia, 2000)

Priority‐Setting Tool Applied to Canada's Landbirds Based on Concern and Responsibility for Species - Erica H. Dunn; David J.T. Hussell; Daniel A. Welsh (Conservation Biology, 1999)
As a contribution to Partners in Flight–Canada, the Canadian Wildlife Service developed a ranking system to help set priorities for landbird species. Two complementary species lists were generated: one with scores for “concern” representing vulnerability and population trend, and one for “responsibility” for regionally characteristic fauna. The concern score gave equal weight to vulnerability, a composite score based on abundance and breadth of range, and population trend, because its purpose was to give early warning of potential problems. Responsibility scores were scale‐free and were assigned for the season in which the species is most abundant. Other systems for identifying species of concern may be more appropriate for other jurisdictions or organisms, but the responsibility ranking is widely applicable. This system is a coarse filter that generates preliminary ranks; additional information should be considered in deciding how to allocate scarce resources for conservation. Unrefined results are nonetheless useful for a variety of purposes, as illustrated by the scores for Canadian landbirds. About 25% of Canada's high‐responsibility species are also of high concern. These high‐concern species are not associated with specific habitats or migration patterns. Conservation of species ranking high on concern and responsibility merits cooperation with the United States and Mexico in particular. The scores identified improved monitoring as a priority conservation activity for Canada.